Checklist of the birds of the Sula Islands, with particular reference to Taliabu Island - A J Stones; R S Lucking; P J Davidson; W Raharjaningtrah (KUKILA, 1997)
The results are presented of a survey conducted on Taliabu, the Sula Islands, Maluku, Indonesia in September October 1991. Apart from two brief visits by single scientists in the previous three years, no ornithological investigations had been conducted in the island group for fifty years. The Sula Islands lie midway between the Sulawesi and Moluccan faunal regions and contain representative species derived from both, with a high degree of endemism at species and subspecies level. The survey recorded 152 bird species, including 47 species new to the islands (a further 8 species have been added to the islands' list by other observers previous to the present survey). While 34 of these may be considered as migrant or vagrant species with no particular significance (including the first record for Indonesia of Black faced Bunting), some 14 additions are considered important. The majority of the latter have Sulawesi affinities and include Lesser Fish eagle, Rufous bellied Eagle, Oriental Hobby, White bellied Imperial Pigeon, Great Eared Nightjar, Citrine Flycatcher, Mountain Tailorbird and Red backed Thrush, whereas the Island Leaf warbler has Moluccan affinities. Records of Snowy browed Flycatcher, Little Pied Flycatcher, Island Flycatcher, Crimson Honey eater and Mountain White eye fill gaps in the known distribution between the two regions. Several of the Sula Island (or Sula Banggai islands) endemics were found to have healthy populations (Sula Scrubfowl, Slaty Cuckoo shrike, Sula Cicadabird, Helmeted Myna and Bare eyed Myna), although both the mynas are apparently uncommon. However, the Sula Pitta (here split from Red bellied Pitta) was considered uncommon, while there was only one observation of the Taliabu Masked Owl, constituting the second known record. More intensive survey work is required to determine the status of this owl. Almost all endemic taxa, however, are dependent upon forest, and proposals have been submitted for the establishment of a reserve covering some 900 sq. km.